Târîh-i harb - Erdemgil, Osman Senai, 1872-1944. (Kostantiniyye [İstanbul] Kostantiniyye [İstanbul])
3 cilt 1 ciltte (1. c. [5], 239 s., 2. c. 191, 12 s., 3. c. 268, [4] s., 31 s. resim, portre, kroki)